Multifunctional metasurfaces integrating near-field display and 3D holography. (1st December 2021) - Du, Wenjuan; Lou, Zhilang; Chen, Xuesong; Chen, Long; Tang, Dongliang
Abstract: Metasurfaces have versatile manipulation capabilities in the optical field and provide the possibility of building a compact optical device with various complex functions. They have been regarded as ideal candidates to construct a miniaturized optical system with high density and multi-channel information. In this work, reflective all-metallic multifunctional metasurfaces consisting of aluminum nanorods are designed by simultaneously realizing the near-filed display and three-dimensional (3D) holography. Specifically, in the proposed design, each nanorod acts as a complex amplitude modulator to provide continuous amplitude control and binary phase control. By carefully optimizing the orientations of nanorods, a multifunctional metasurface can be designed to display a near-field grayscale pattern and far-field 3D images simultaneously. Numerical results by a full-wave simulation validate the good performance of the proposed design. The proposed method could provide greater degree of freedom to designs of lightweight devices, which could be employed in optical applications, such as virtual or augmented reality displays and anti-counterfeiting technology.